Enhanced thermoelectric performance of CNT/P3HT composites with low CNT content. Issue 59 (2nd October 2018) - Qu, Sanyin; Wang, Mengdi; Chen, Yanling; Yao, Qin; Chen, Lidong
Abstract : The maximum TE power factor of CNT ( d < 8 nm)/P3HT composite films reached 49.0 μW mK −2 at the mass fraction of 5 wt% CNTs. Abstract : Carbon nanotubes (CNTs) have emerged as one of the leading additives for improving the thermoelectric properties of organic materials due to their unique structure and excellent electronic transport properties. However, since as-grown CNTs generally possess different diameters, it is of high interest to determine the influence of the diameter of carbon nanotubes on the thermoelectric properties of CNT/poly(3-hexylthiophene) (P3HT) composite films. Herein, we prepared CNT/P3HT composite films with diameters of <8 nm, 8–15 nm, 20–30 nm, 30–50 nm and >50 nm and studied their thermoelectric properties. It was found that the diameter of CNTs had an important influence on the TE performance of the composite films. The P3HT- d CNT (<8 nm) and P3HT- d CNT (8–15 nm) composite films exhibited almost the same thermoelectric performance and almost more than double that of the other three composite films with increased CNT diameter. The different mass fractions of CNT/P3HT composite films have also been investigated. The maximum TE power factor of CNT ( d < 8 nm)/P3HT composite films reached 49.0 μW mK −2 at the mass fraction of 95 wt% P3HT, that is, 5 wt% CNTs. This superior TE power factor of CNT ( d < 8 nm)/P3HT composite films can be ascribed to the fully connected interlayer of the P3HT polymer and also the heterogeneous dispersion of short-length CNTs.